Effect of potassium on nutritional status and productivity of peanuts in succession with sugarcane - Almeida, H. J. [UNESP]; Pancelli, M. A. [UNESP]; Prado, R. M. [UNESP]; Cavalcante, V. S. [UNESP]; Cruz, F. J.R. [UNESP] (Springer Nature, 2015)
Potassium contained in sugarcane straw quickly returns to the soil in a form readily available to crops. Thus, the objective of this study was to evaluate the effect of potassium on the nutritional status and grain yield of peanutscultivated in succession with sugarcane harvested without burning. The experiment was installed in Jaboticabal, São Paulo, Brazil, in Dystrophic Red Latosolcultivated with the peanut crop, variety Runner IAC 886. The treatments consisted of the application of 30, 60, 90 and 120 kg ha-1 of K2 O and a control (no potassium). The experimental design adopted consisted of randomized blocks with five replications. Parameters evaluated were height, diameter, number of leaves, nutritional status for potassium and grain yield. Potassium resulted in a significant increase in the number of leaves and height, K contents (50-70 g kg-1) and grain yield, obtaining 2790 kg ha-1 at a dose of 120 kg ha-1. The sugarcane straw alone is not sufficient to meet the nutritional needs of peanuts planted in succession with sugarcane, where application of potassium fertilizer is necessary to obtain high yields.Potassium fertilization improved the nutritional status and was reflected in the increased production of grains of peanuts grown in rotation with sugarcane, especially at the dose of 120 kg ha-1 K2 O.
Keywords: Conservation management; Grain; Potassium fertilizer; Straw